2017
DOI: 10.1186/s12884-017-1580-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal characteristics and birth outcomes resulting from births before arrival at health facilities in Nkangala District, South Africa: a case control study

Abstract: BackgroundRisks of severe, avoidable maternal and neonatal complications at birth are increased if the birth occurs before arrival at the health facility and in the absence of skilled birth attendants. Birth Before Arrival (BBA) is a preventable phenomenon still common in modern-day practice despite extensive improvements made in obstetric care and in accessibility to healthcare in South Africa. This study aimed to determine the risk factors and outcomes in mothers and babies associated with being born before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 9 publications
5
11
0
2
Order By: Relevance
“…Over the study period, the incidence of OHD in this study was 0.22%, which is similar to that reported in other studies ( Table 4 ), and our findings were in line with previous studies of accidental OHDs [ 1 8 , 11 ]. OHDs have been reported to be associated with the risk of prematurity [ 1 3 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Over the study period, the incidence of OHD in this study was 0.22%, which is similar to that reported in other studies ( Table 4 ), and our findings were in line with previous studies of accidental OHDs [ 1 8 , 11 ]. OHDs have been reported to be associated with the risk of prematurity [ 1 3 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Multiparous mothers and lack of prenatal care were also related to OHDs in previous reports [ 1 – 5 , 9 ]. Furthermore, OHDs may cause high neonatal mortality and morbidity, especially in developing countries and areas short of medical assistance [ 11 ]. Prompt intervention and care may be required for all OHD neonates to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…46.0% of BBA mothers had abnormal mode of previous delivery compared with 19.4% of hospital delivered mothers. The findings are consistent with studies which found previous history of precipitate delivery, BBA and preterm birth puts a woman at risk of BBA [3,8]. The study established significant statistical tal birth outcome.…”
Section: Bba and Hospital Birth Outcomesupporting
confidence: 91%
“…Slightly more than half (54.1%) of BBA mothers were unemployed compared with 45.9% of hospital delivered mothers. The findings are consistent with study conducted in South Africa which found occupation not a risk factor for BBA [3]. The findings are inconsistent with study conducted in Coast general hospital which found occupation (being house wife) to be a risk factor for BBA [13].…”
Section: Bba and Hospital Birth Outcomesupporting
confidence: 59%
See 1 more Smart Citation